On the self-organizing of reality-totality as living knowledge - Tassinari, Ricardo Pereira [UNESP] (Taylor & Francis, 2018)
In this chapter, it is argued that reality as a totality may be conceived as a living and active knowing, and as the self-exposing idea, which is a self-organized process of which our own knowing is part. Although this philosophical view goes beyond a mere epistemological analysis of self-organized processes and enters into a metaphysical viewpoint, it is shown that the chapter’s conclusions follow from very natural assumptions and reflections about the constitution of scientific knowledge. This philosophical view constitutes a systemic perspective that makes possible the coordination of a diversity of scientific methods and contents.